Nonperturbative gluon exchange in pp elastic scattering at TeV energies - Bopsin, G. B.; Luna, E. G.S.; Natale, A. A. [UNESP]; Peláez, M. (American Physical Society (APS), 2023)
We investigate the two-gluon-exchange model of the Pomeron using nonperturbative gluon propagators characterized by a dynamical mass scale. We present the results for an analysis of the available pp differential cross section data at TeV energies which accounts for dynamical gluon masses obtained from a nonlinear version of the Schwinger-Dyson equations. We show that our two-gluon exchange model gives an excellent description of the LHC data, provided we demand the Reggeization of the scattering amplitude and make a suitable choice for the convolution of proton wave functions.